Potention and Substained Utilization Effort of Medicinal Plants in Meru Betiri National Park - Tri Wibowo; Puja Utama; Ervizal AMZU (Media Konservasi, 1991)
Mend Betiri National Park is a conservation area inhabited by various jind of genetic resource, among others medicinal plants. Such areacontain less 88 medicinal plant species that potensially plqys a role as genetic resource for devoloprnent efforts of medicinal plants cultivation out of the national park area. The pattern of sustainable utilization of genetic resource in Meru Betin'National Park is buffer zone management. In such area, the people are giuded to grow medicinal plants where is seeh are gained from the national park The plants that had been tried to be grown in buffer zone area were cube jawa (&Pretrofractum) and kemuhs (Piper cubeba)